The praier and complaynte of the ploweman unto Christe - Parker, Douglas H. (Douglas Harold), 1942- (University of Toronto Press, 1997)
Sixteenth-century English Protestant reformers were hard-pressed to establish a historical pedigree that would provide their ideas with weight and legitimacy. Many of those reformers turned back to early fifteenth-century Lollard texts, recycling and reprinting them to serve the needs, both political and spiritual, of the burgeoning English Protestant reform movement. The anti-clerical and reformist Lollard text, The praier and complaynte of the ploweman vnto Christe, was one of the works used by sixteenth century English Protestants in their struggle for religious reform. This is an old-spelling, critical edition of the version of The praier and complaynte of the ploweman vnto Christe that resurfaced in the 1530s. Demonstrating the continuity of ideas between the Lollards and the Reformists, Douglas Parker situates The praier and complaynte firmly in the tradition of English Reformist borrowing of texts, and argues for William Tyndale as editor of the sixteenth-century version of The praier and complaynte. Parker examines the two extant copies of the manuscript, and comments on the work's structure and reformist content. He presents full historical, literary, and biographical information in his introduction, and a full line-by-line commentary on the text.This careful, meticulous work is a revealing look at the ideology of Protestant religious struggles in England from the fourteenth to the sixteenth century.